Diary of a television viewer. Issue 1 (February 2017) - Griffen-Foley, Bridget
In 1974, Melbourne teenager Jennifer Sketchley started keeping a daily diary. It continued until 1985, describing everyday life as a schoolgirl, leaving school at the age of 16, studying by correspondence and entering the workforce. She was happiest watching films and television, with her diary recording what she watched from morning to night. Sketchley's diaries provide an intimate insight into the television habits and preferences of one Australian. This girl-centred article frames this unique record within the context of her family circumstances and within the field of girls' media studies. It examines the everyday practice of an active television consumer and fan, engaging with programmes (especially Star Trek ) and television periodicals, and seeking comfort and community.